2013
DOI: 10.1590/s1413-35552013005000097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the user satisfaction level in a public physical therapy service

Abstract: The final values of the GGUH physical therapy department showed that patients can be satisfied even in a public health service. Satisfaction measures must have a multidimensional approach, and we found that people with more years of study showed lower values of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(45 reference statements)
0
4
0
4
Order By: Relevance
“…Esse tipo de análise que inclui o usuário no centro do processo avaliativo, como agente transformador, é fundamental para permitir um redirecionamento de estratégias de gestão da saúde pública [9][10][11][12][13]29]. No Brasil e no mundo, investigações com diferentes métodos têm sido feitas com esse propósito [10,12,19,[26][27][28][29][30][31][32].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esse tipo de análise que inclui o usuário no centro do processo avaliativo, como agente transformador, é fundamental para permitir um redirecionamento de estratégias de gestão da saúde pública [9][10][11][12][13]29]. No Brasil e no mundo, investigações com diferentes métodos têm sido feitas com esse propósito [10,12,19,[26][27][28][29][30][31][32].…”
Section: Discussionunclassified
“…Estudos têm sido conduzidos no sentido de avaliar a percepção dos usuários a respeito dos serviços de saúde, em nível nacional [10,16,19,[26][27][28] e internacional [29][30][31][32]. Essas pesquisas apontam com principais aspectos negativos a falta de tempo despendido por parte dos profissionais [27,29] e problemas com infraestrutura [27].…”
Section: Introductionunclassified
“…La revisión sistemática realizada por Enkhjargal Batbaatar, demuestra relación (Batbaatar, Dorjdagva, Luvsannyam, & Amenta, 2017). El estudio de Renato S. Almeida no encontró asociación con el grupo etario (Almeida, Nogueira, & Bourliataux-Lajoine, 2013). El Hospital II atiende a pacientes asegurados, que en su mayoría lo conforman adultos, población económicamente activa, sin asistencia frecuente a los establecimientos de salud que sí lo realiza el adulto mayor, influenciando en la satisfacción de los usuarios.…”
Section: Discussionunclassified
“…To achieve such a harmonized relationship, physical therapists should develop good communication skills to ensure a better understanding of each patient 11 . Some studies have shown that patients with neurological impairments require a greater commitment by their physiotherapist and greater understanding that comes from interpersonal communication 17 . The satisfaction of patients is affected by many factors, most of which derive from communication with healthcare professionals.…”
Section: Review Article / Pregledni čLanakmentioning
confidence: 99%
“…Patient need is to feel the emotional balance in the relationship in order to increase efficiency in conducting the therapy. Most patient's dissatisfactions resulting from lack of communication physiotherapist with them during the treatment, which is then reduced only to the physical component 17 . Communication with sick people is based on trust that is built through a quality relationship, active listening, conversation skills and empathy and words that will console patients.…”
Section: Review Article / Pregledni čLanakmentioning
confidence: 99%